Reinventing State Capitalism - Aldo Musacchio, Sergio G. Lazzarini (Harvard University Press, 2014)
How have the new forms of state capitalism evolved over the years? For some observers, the rise of state capitalism to the forefront of global markets is a consequence of the global fi nancial crisis that started in 2008. Bremmer (2010), for instance, sees that crisis as a shock that led to an alarming reemergence of state capitalism. Part of the concern comes from the fact that, even in a liberal economy such as the United States, the crisis led the government to bail out fi rms such as General Motors and AIG, a large insurance group, becoming a minority shareholder of the former and a majority shareholder of the latter. As the examples of Agricultural Bank of China and JBS illustrate, however, state capitalism was alive and kicking— and even expanding—before the crisis (Amatori et al. 2011; Bortolotti and Faccio 2009). Firms owned and operated by the government were privatized en masse in the 1980s, 1990s, and early 2000s, but state own ership and infl uence in those fi rms continued. State capitalism peaked in the middle of the 1970s when Eu ro pe an governments nationalized fi rms in large numbers. Around the same time, governments in developing countries either nationalized fi rms or created (and then owned) tens or hundreds of new ones. As a consequence, by the end of the 1970s, SOE output to GDP reached 10 percent in mixed economies and close to 16 percent in developing countries.